2017
DOI: 10.1038/s41598-017-08205-5
|View full text |Cite
|
Sign up to set email alerts
|

Population pharmacokinetics of peginterferon α2a in patients with chronic hepatitis B

Abstract: There were significant differences in response and pharmacokinetic characteristics to the peginterferon α2a treatment among Chronic Hepatitis B (CHB) patients. The aim of this study is to identify factors which could significantly impact the peginterferon α2a pharmacokinetic characteristics in CHB patients. There were 208 blood samples collected from 178 patients who were considered as CHB and had been treated with peginterferon α2a followed by blood concentration measurement and other laboratory tests. The co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…the population). 2 The characteristics of many patients (covariates), such as the state of the disease, demographics, concomitant medications, or the presence of renal or hepatic impairment, can all have an effect on drug pharmacokinetics. Therefore, it is essential to understand this variability to help guide safe and effective dosing regimens.…”
Section: Introductionmentioning
confidence: 99%
“…the population). 2 The characteristics of many patients (covariates), such as the state of the disease, demographics, concomitant medications, or the presence of renal or hepatic impairment, can all have an effect on drug pharmacokinetics. Therefore, it is essential to understand this variability to help guide safe and effective dosing regimens.…”
Section: Introductionmentioning
confidence: 99%
“…Low vancomycin concentration can lead to treatment failure, so it is necessary to study the correlation between BMI and the concentration of vancomycin. Indeed, there were studies already had shown that Vd was associated with BMI, and drug clearance (CL) had a positive correlation with CrCl [25,26]. Hence, we speculate that the effect of BMI on vancomycin 9 concentration may be achieved by affecting the Vd, while the effect of CrCl on vancomycin concentration was mainly achieved by affecting the drug CL.…”
Section: Discussionmentioning
confidence: 82%
“…Low vancomycin concentration can lead to treatment failure, so it is necessary to study the correlation between BMI and the concentration of vancomycin. Indeed, there were studies already had shown that Vd was associated with BMI, and drug clearance (CL) had a positive correlation with CrCl [25,26]. Hence, we speculate that the effect of BMI on vancomycin concentration may be achieved by affecting the Vd, while the effect of CrCl on vancomycin concentration was mainly achieved by affecting the drug CL.…”
Section: Discussionmentioning
confidence: 82%